The Effect of Single and Double Activation with Potassium Hydroxide 2N on Charcoal from Fir Wood (Casuarina Junghuhniana) Pyrolysis - Siti Jamilatun; Eva Nurdiana Putri; Zulia Arifah; Ilham Mufandi (CHEMICA: Jurnal Teknik Kimia, 2020)
The purpose of this study was to know the influence of the single and double activation by using calcium hydroxide (KOH) with a concentration of 2N. The activation of KOH 2N applied in the activated carbon from pine wood. The activated carbon made through the pyrolysis process with a temperature variation of 500-600 â„ƒ for about 180 minutes. The experiment performed in two ways: (i) single activation of KOH 2N and (ii) double activation of KOH 2N.Â  The effects of ash content and Iod absorption content in activated carbon were studied. The results showed that the ash content about 8-30% and Iod absorption content about 317.25-507.60 mg Iod/gram carbon. The results of this study standardized by using the Indonesia National Standards (SNI) method. The result also indicated that the single activation was better than double activation of KOH.